1987
DOI: 10.1159/000132372
|View full text |Cite
|
Sign up to set email alerts
|

Problems in using Robertsonian rearrangements in determining monophyly: examples from the genera <i>Tatera </i>and <i>Gerbilluru</i><i>s</i>

Abstract: Chromosomal banding data on three species of Tatera from Kenya significantly alter the previous hypothesis of relationships between and within the genera Tatera and Gerbillurus based on cladistic analyses and the rule of parsimony (Qumsiyeh, 1986b). Of the many possible hypothetical relationships, the most parsimonious tree showed three homoplasies and allowed the genus Gerbillurus to be paraphyletic. The alternative trees, depicting larger number of homoplasies but with homoplasies restricted to fusion or fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 11 publications
(12 reference statements)
2
16
1
Order By: Relevance
“…The monophyly of Gerbilliscus and Gerbillurus (here represented by G. tytonis , in addition to G. paeba and G. vallinus already studied by Qumsiyeh et al, 1987) shown by this analysis is not surprising as it was suggested by earlier chromosomal (Qumsiyeh, 1986;, morphological (Pavlinov, 2001;Pavlinov et al, 1990) and molecular (Chevret, 1994;Chevret and Dobigny, 2005;Colangelo et al, 2007) studies. In fact, even the close relationship between these two genera was first suggested on the basis of comparative banding analysis (Qumsiyeh et al, 1987).…”
Section: Karyotype Evolution and Phylogenetic Relationshipssupporting
confidence: 67%
See 3 more Smart Citations
“…The monophyly of Gerbilliscus and Gerbillurus (here represented by G. tytonis , in addition to G. paeba and G. vallinus already studied by Qumsiyeh et al, 1987) shown by this analysis is not surprising as it was suggested by earlier chromosomal (Qumsiyeh, 1986;, morphological (Pavlinov, 2001;Pavlinov et al, 1990) and molecular (Chevret, 1994;Chevret and Dobigny, 2005;Colangelo et al, 2007) studies. In fact, even the close relationship between these two genera was first suggested on the basis of comparative banding analysis (Qumsiyeh et al, 1987).…”
Section: Karyotype Evolution and Phylogenetic Relationshipssupporting
confidence: 67%
“…kempi (Codjia et al, 1994;Colangelo et al, 2001). Similarly, G. robustus in the Central African Republic (Matthey and Petter, 1970) and G. kempi in Guinea (Gautun et al, 1986) were both characterized by 2n = 46, whereas other authors attributed a 2n = 36 karyotype to the former species (Qumsiyeh et al, 1987;Granjon and Dobigny, 2003;Colangelo et al, 2005) and 2n = 48 karyotype to the latter (Codjia et al, 1994;Colangelo et al, 2001). Not surprisingly, this has resulted in inaccuracies in recent taxonomic lists of the genus Carleton, 1993, 2006), where the inclusion of certain species is clearly questionable from a chromosomal point of view.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is well supported by the CI, RI, RC and g1 statistics and by bootstrap and decay index values. In addition, the majority of the chromosome changes inferred correspond to Robertsonian changes, something which is commonly observed in mammals including gerbilline rodents (Qumsiyeh et al, 1987). More importantly, the cladistic method used here implies that character changes are not polarized a priori, thus allowing both fusions and fissions to be inferred (reviewed in Dobigny et al, 2004a).…”
Section: Discussionmentioning
confidence: 98%